Real-Time operating systems and programming languages for embedded systems - Orozco, Javier Dario (2012)
In this chapter, we present the different alternatives that are available today for the development of real-time embedded systems. In particular, we will focus on the programming languages use like C++, Java and Ada and the operating systems like Linux-RT, FreeRTOS, TinyOS, etc. In particular we will analyze the actual state of the art for developing embedded systems under the WORA paradigm with standard Java [1], its Real-Time Specification and with the use of Real-Time Core Extensions and pico Java based CPUs [5]. We expect the reader to have a clear view of the opportunities present at the moment of starting a design with its pros and cons so it can choose the best one to fit its case.